Paint Defects Pada Pintu Pengelak Proyek Bendungan Tiga Dihaji Di PT. Barata Indonesia (Presero) Divisi Sumber Daya Air - Gleni Anita Rani; Hadi Wibowo (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
PT Barata Indonesia (Persero) is a state-owned enterprise in the manufacturing and industrial engineering sector, one of which produces sluice gates for water control systems in dams. An important stage in the production process is coating, which serves to protect metals from corrosion. The quality of the coating significantly affects the durability and occurrence of paint defects such as blistering, cracking, peeling, orange peel, sagging, and the overall product lifespan. However, defects like pinholes are often found in practice. These defects are generally caused by suboptimal surface preparation, application errors, unsuitable environmental conditions, and improper drying processes. During an internship at PT Barata Indonesia, Division of Water Resources, the author directly observed the coating process of sluice gates for the Tiga Dihaji Dam project. This study identifies the types of paint defects, analyzes their causes, and provides recommendations for improvement in coating and product durability for national infrastructure projects. Keywords: paint defects, coating process, painting defects.   Abstrak PT Barata Indonesia (Persero) merupakan BUMN yang bergerak di bidang manufaktur dan rekayasa industri, salah satunya memproduksi pintu pengelak (sluice gate) untuk sistem pengendalian air pada bendungan. Salah satu tahap penting dalam produksi adalah proses pengecatan (coating) yang berfungs melindungi logam dari korosi. Kualitas pengecatan sangat memengaruhi daya tahan pengecatan (paint defects) seperti blistering, cracking, peeling, orange peel, sagging, dan umur pakai produk. Namun, pada praktiknya sering ditemukan cacat dan pinhole Cacat ini umumoya disebabkan oleh persiapan permukaan yang kurang optimal, kesalahan aplikasi, kondisi lingkungan yang tidak sesuai, serta proses pengeringan yang tidak tepat. Melalui kegiatan magang di PT Barata Indonesia Divisi SDA, penulis mengamati langsung proses pengecatan pintu pengelak untuk proyek Bendungan Tiga Dihaji. Penelitian ini mengidentifikası jenis cacat pengecatan, menganalisis penyebabnya, serta memberikan rekomendasi perbaikan. pengecatan dan ketahanan produk pada proyek-provek infrastruktur nasional. Kata Kunci: paint defects, proses pengecetan, cacat pengecetan.